Glass-ceramic frosting powder with AG flashing effect as well as preparation method and application of glass-ceramic frosting powder
Through the combination technology of fluoride, acidic additives and passivating agents, the problem of poor frosting effect when used on microcrystalline glass is solved, and the uniform flash sand surface and high privacy effect of microcrystalline glass are achieved.
Patent Information
- Application Number
- CN202411897506.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
When used on crystal crystal glass, the frosting effect is poor, the appearance is single and no flash effect, and the sand surface is rough, making it easy to remain dirt.
Using scientific combination of fluoride, acidic additives and passivating agents, through the etching effect of fluoride on the glass, the acidic additive provides hydrogen ions and fluoride ions to form hydrofluoric acid etching glass. The passivating agent generates fine, uniform, multi-faceted three-dimensional particles to form a uniform flash sand surface.
It achieves the privacy effect of uniform flash sand surface after etching of microcrystalline glass, small roughness, smooth surface, anti-scratch and high haze. The sand surface is delicate and does not easily retain dirt, which is significantly better than commercially available frosting powder.
Smart Images

Figure CN119707306A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass etching, and in particular relates to AG flash effect frosting powder of microcrystalline glass and a preparation method and application thereof. Background Art
[0002] Common bathroom glass doors and windows use ordinary transparent tempered glass to achieve the function of water blocking and partitioning, and physical privacy film is pasted or sprayed on the glass surface to protect privacy. However, physical privacy film is easily scratched or aged, has a short service life, and loses its function of protecting privacy. At the same time, ordinary tempered glass is easy to crack and break after being hit.
[0003] With the improvement of the quality of life, consumers have higher and higher requirements for the durability and aesthetics of bathroom glass, and new materials are constantly being developed for bathroom glass, among which microcrystalline glass is more and more widely used. After high-temperature treatment, microcrystalline glass forms a fine microcrystalline structure. The microstructure and performance are different from those of glass and ceramics, and it has higher strength and hardness than tempered glass. And because microcrystalline glass can use ore, industrial tailings, metallurgical slag, fly ash, etc. as the main production raw materials, it can achieve the overall utilization and zero emission of solid waste. The product itself has no radioactive pollution, so it is also called environmentally friendly material or green material. After AG frosting treatment, microcrystalline glass is used in bathroom glass. It has the characteristics of high hardness, good privacy effect, scratch resistance, and fashionable appearance, and is deeply loved by consumers.
[0004] The glass frosting powder currently available on the market is mainly designed for conventional glass. When it is used to frost microcrystalline glass, the resulting frosting effect is poor, with a simple appearance, no glittering effect, and a lack of fashionable decorativeness. The few products with glittering decorative effects have the problems of rough frosting, insufficient surface fineness, and easy residual dirt. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide an AG flash effect frosting powder for microcrystalline glass.
[0006] The frosting powder of the present invention is specially designed for the structural particularity of microcrystalline glass. Different passivators and compounded acid additives are used. Through the scientific compounding of fluoride, acid additives, passivators and water, the microcrystalline glass can be etched to have a uniform shiny sand surface, small roughness, smooth surface, anti-scratch, high haze and good privacy effect.
[0007] Another object of the present invention is to provide a method for preparing the AG flash effect frosting powder of the above-mentioned microcrystalline glass.
[0008] Another object of the present invention is to provide the use of the above-mentioned AG flash effect frosting powder in glass etching, which can be applied to the frosting of bathroom microcrystalline glass.
[0009] The frosting powder of the present invention uses the etching effect of fluoride on glass, and under the joint action of the acidic auxiliary agent and the passivating agent, a uniform and stable AG frosting effect is formed. The microcrystalline glass treated with the frosting powder of the present invention has the advantages of uniform sand mold after frosting, uniform appearance and stable parameters, etc. The roughness of the treated glass is 0.1-0.2μm, the haze is 90%-100%, and it has a delicate frosted surface with a cool flashing effect. Compared with the AG glass made of commercially available frosting powder, it has the advantages of finer sand mold, smoother sand surface, and stable parameters. It is applied to bathroom glass to obtain good privacy and decorative effects, and the use experience effect is excellent.
[0010] The purpose of the present invention is achieved through the following solutions:
[0011] In a first aspect, a frosting powder with AG flash effect for microcrystalline glass includes the following raw material components by weight percentage: fluoride: 40% to 50%; acid auxiliary agent: 30% to 40%; passivating agent: 10% to 30%.
[0012] As a solution of the present invention, the above-mentioned fluoride may include at least one of ammonium fluoride and potassium hydrogen fluoride.
[0013] As a solution of the present invention, the above-mentioned acid adjuvant may include at least one of lactic acid, phytic acid, and gluconic acid.
[0014] As a solution of the present invention, the above-mentioned passivating agent may include at least one of cassava starch, wheat starch, and mung bean starch.
[0015] The fluoride in the frosting powder of the present invention is slowly partially dissolved in water during use, and can provide separated fluoride ions to combine with hydrogen ions to form hydrogen fluoride, which can corrode or even dissolve glass, and is an effective component for glass frosting; the acidic auxiliary agent is dissolved in water to provide hydrogen ions, which combine with the fluoride ions released by the fluoride to form hydrofluoric acid to etch the glass; the lactic acid, phytic acid, gluconic acid and the like used in the present invention not only realize the function of providing hydrogen ions, but also have the effect of regulating the viscosity of the agent, play a role in slowing down the stratification of the agent, help to evenly etch the glass surface, generate uniform and stable microscopic particles, and obtain ideal frosted glass. Further, the frosting powder of the present invention is also added with a passivator, cassava starch, wheat starch, mung bean starch, etc. are dissolved and dispersed in water, and the components in the formula of the frosting powder reach a saturated state in the etching solution during use, and the consumption and dissolution during use are in dynamic equilibrium, and the undissolved solids suspended in the etching solution are wrapped into countless tiny particles by the passivator, thereby significantly improving the stability of the use of the agent, and the particles are deposited on the glass surface, and the inert passivator does not react with the glass, thereby preventing the glass from etching, and playing a passivation effect, and the glass surface that is not covered with particles will have an etching effect, and the automatic frosting equipment swings regularly, and the glass is in a dynamic etching, forming a uniform and stable etching surface, which is microscopically small and uniform multi-faceted three-dimensional particles, and the flashing effect is good. The addition of the passivator in the present invention effectively prevents the local excessive corrosion of the glass, and avoids the problems of microscopic unevenness, large roughness, and rough and unsophisticated surface caused by excessive corrosion.
[0016] In a second aspect, a method for preparing the AG flash effect frosting powder of the above-mentioned microcrystalline glass is provided, and the product can be obtained by uniformly mixing the components in proportion.
[0017] In a third aspect, the application of the AG flash effect frosting powder of the above-mentioned microcrystalline glass in glass etching may specifically include the following steps: adding the AG flash effect frosting powder of the present invention into water, stirring and dissolving it, and then etching the glass to be etched.
[0018] As a solution of the present invention, the mass ratio of frosting powder: water is 5:0.5-5:1.5; preferably 5:1.
[0019] Furthermore, after adding the frosting powder to water, it can be heated and stirred to accelerate dissolution, for example, it can be heated in a water bath at 40-60°C and stirred for 24 hours for use.
[0020] As a solution of the present invention, the etching treatment uses a temperature of 10-25° C., a frosting time of 60-90 seconds, and a frosting swing frequency of the frosting equipment of 1-2 times / second.
[0021] The frosting powder of the present invention improves the traditional frosting powder, adds a passivator to generate fine and uniform multi-faceted three-dimensional particles, and compounding acidic additives to provide hydrogen ions and fluorine ions to etch glass, and also has the effect of regulating the viscosity of the agent, plays a role in slowing down the stratification of the agent, and helps to etch the glass surface uniformly, and avoids the rapid and irregular deposition of a large amount of powder on the glass to affect the etching effect. Through the scientific compounding of fluoride, acidic additives, passivators and water, the microcrystalline glass can be etched to have a uniform shining sand surface, small roughness, smooth surface, anti-scratch, high haze and good privacy effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0023] Figure 1-Figure 2 These are macroscopic images and microscope photographs of the AG effect frosted glass prepared by the present invention.
[0024] Figure 3-Figure 4 These are macro and microscopic images of traditional frosted glass. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. The materials involved in the following examples can be obtained from commercial channels unless otherwise specified. The methods described are conventional methods unless otherwise specified.
[0026] Example 1
[0027] The invention discloses AG flashing effect frosting powder for bathroom microcrystalline glass, which comprises the following raw material components by weight percentage: 30% of ammonium fluoride, 20% of potassium hydrogen fluoride, 28% of lactic acid, 10% of cassava starch and 12% of wheat starch.
[0028] Add the raw materials in order according to the frosting powder formula and mix them evenly. According to the mass ratio of frosting powder: water = 5:1, the solid slowly dissolves in water. Heating at 50℃ in a water bath can speed up the dissolution rate. Use it after stirring with an automatic stirring device for 24 hours.
[0029] Frosting treatment:
[0030] (1) The side of the original microcrystalline glass sheet that does not need to be etched is protected by silk-screen coating with anti-etching ink;
[0031] (2) placing the original glass-ceramic sheet into an automatic frosting device, controlling the temperature of the frosting powder at 10-25° C., the frosting time at 60-90 seconds, and the frosting swing frequency of the automatic frosting device at 1-2 times / second;
[0032] (3) After etching, the glass is cleaned with pure water and dried to obtain a frosted glass.
[0033] Example 2
[0034] The invention discloses AG flashing effect frosting powder for bathroom microcrystalline glass, which comprises the following raw material components by weight percentage: 47% ammonium fluoride, 23% potassium hydrogen fluoride, 12% gluconic acid and 18% mung bean starch.
[0035] Add the raw materials in order according to the frosting powder formula and mix them evenly. According to the mass ratio of frosting powder: water = 5:1, the solid slowly dissolves in water. Heating at 50℃ in a water bath can speed up the dissolution rate. Use it after stirring with an automatic stirring device for 24 hours.
[0036] Frosting treatment:
[0037] (1) The side of the original microcrystalline glass sheet that does not need to be etched is protected by silk-screen coating with anti-etching ink;
[0038] (2) placing the original glass-ceramic sheet into an automatic frosting device, controlling the temperature of the frosting powder at 10-25° C., the frosting time at 60-90 seconds, and the frosting swing frequency of the automatic frosting device at 1-2 times / second;
[0039] (3) After etching, the glass is cleaned with pure water and dried to obtain a frosted glass.
[0040] Example 3
[0041] The invention discloses an AG flash effect frosting powder for bathroom microcrystalline glass, comprising the following raw material components by weight percentage: 25% potassium hydrogen fluoride, 20% ammonium fluoride, 10% phytic acid, 15% lactic acid, 12% gluconic acid, 7% cassava starch and 11% mung bean starch.
[0042] Add the raw materials in order according to the frosting powder formula and mix them evenly. According to the mass ratio of frosting powder: water = 5:1, the solid slowly dissolves in water. Heating at 50℃ in a water bath can speed up the dissolution rate. Use it after stirring with an automatic stirring device for 24 hours.
[0043] Frosting treatment:
[0044] (1) The side of the original microcrystalline glass sheet that does not need to be etched is protected by silk-screen coating with anti-etching ink;
[0045] (2) placing the original glass-ceramic sheet into an automatic frosting device, controlling the temperature of the frosting powder at 10-25° C., the frosting time at 60-90 seconds, and the frosting swing frequency of the automatic frosting device at 1-2 times / second;
[0046] (3) After etching, the glass is cleaned with pure water and dried to obtain a frosted glass.
[0047] Example 4
[0048] A frosting powder with AG flashing effect for bathroom microcrystalline glass comprises the following raw material components by weight percentage: 40% potassium hydrogen fluoride, 20% phytic acid, 16% lactic acid, 15% cassava starch and 9% mung bean starch.
[0049] Add the raw materials in order according to the frosting powder formula and mix them evenly. According to the mass ratio of frosting powder: water = 5:1, the solid slowly dissolves in water. Heating at 50℃ in a water bath can speed up the dissolution rate. Use it after stirring with an automatic stirring device for 24 hours.
[0050] Frosting treatment:
[0051] (1) The side of the original microcrystalline glass sheet that does not need to be etched is protected by silk-screen coating with anti-etching ink;
[0052] (2) placing the original glass-ceramic sheet into an automatic frosting device, controlling the temperature of the frosting powder at 10-25° C., the frosting time at 60-90 seconds, and the frosting swing frequency of the automatic frosting device at 1-2 times / second;
[0053] (3) After etching, the glass is cleaned with pure water and dried to obtain a frosted glass.
[0054] Example 5
[0055] The invention discloses AG flashing effect frosting powder for bathroom microcrystalline glass, comprising the following raw material components by weight percentage: 38% ammonium fluoride, 18% gluconic acid, 16% lactic acid, 11% cassava starch and 17% wheat starch.
[0056] Add the raw materials in order according to the frosting powder formula and mix them evenly. According to the mass ratio of frosting powder: water = 5:1, the solid slowly dissolves in water. Heating at 50℃ in a water bath can speed up the dissolution rate. Use it after stirring with an automatic stirring device for 24 hours.
[0057] Frosting treatment:
[0058] (1) The side of the original microcrystalline glass sheet that does not need to be etched is protected by silk-screen coating with anti-etching ink;
[0059] (2) placing the original glass-ceramic sheet into an automatic frosting device, controlling the temperature of the frosting powder at 10-25° C., the frosting time at 60-90 seconds, and the frosting swing frequency of the automatic frosting device at 1-2 times / second;
[0060] (3) After etching, the glass is cleaned with pure water and dried to obtain a frosted glass.
[0061] Comparative Example 1
[0062] A frosting liquid comprises the following raw material components by weight percentage: 28% ammonium hydrogen fluoride, 10% barium sulfate, 8% calcium fluorosilicate, 10% hydrochloric acid, 12% potassium silicate, and the balance water.
[0063] The frosting treatment method is the same as above.
[0064] Comparative Example 2
[0065] A frosting liquid comprises the following raw material components by weight percentage: 6% sodium fluoride, 7% calcium fluoride, 6% sodium hydrogen fluoride, 10% polyethylene glycol 400, 6% potassium silicate, 8% barium chloride, 10% boric acid, 12% sulfuric acid, and the balance water.
[0066] The frosting treatment method is the same as above.
[0067] Comparative Example 3
[0068] A frosting liquid comprises the following raw material components by weight percentage: 30% aluminum fluoride, 5% fluorite powder, 5% calcium sulfate, 5% polyethylene glycol 400, 8% sodium silicate, 15% nitric acid, 25% phosphoric acid, and the balance water.
[0069] The frosting treatment method is the same as above.
[0070] Performance Test:
[0071] The performance of the bathroom microcrystalline glass prepared in Examples 1 to 5 and Comparative Examples 1 to 3 was tested before and after etching. The results are shown in Tables 1 and Figure 1-Figure 4 shown. Figure 1 This is a macroscopic picture of the AG flash effect frosted glass prepared in the present invention. Figure 2 This is a microscope photo of the AG flash effect frosted glass prepared in the present invention. Figure 3 This is a macro image of traditional frosted glass. Figure 4 This is a microscope photo of traditional frosted glass.
[0072] Table 1
[0073]
[0074] From Table 1 and Figure 1-Figure 4It can be seen that the bathroom microcrystalline glass obtained by treating the frosting powder of the present invention has the effects of uniform sand mold after frosting, uniform shiny appearance, fine sand surface, smooth surface and not easy to remain dirt. It is applied to bathroom glass to obtain good privacy and decorative effects, and the use experience is excellent.
[0075] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A AG flash effect frosting powder for glass-ceramics, characterized in that The raw material components calculated by weight percentage are as follows: fluoride: 40% to 50%; acid auxiliary agent: 30% to 40%; passivating agent: 10% to 30%.
2. The AG flash effect frosting powder of glass-ceramics according to claim 1, characterized in that: The fluoride includes at least one of ammonium fluoride and potassium bifluoride.
3. The AG flash effect frosting powder of glass-ceramics according to claim 1, characterized in that: The acidic auxiliary agent includes at least one of lactic acid, phytic acid and gluconic acid.
4. The AG flash effect frosting powder of glass-ceramics according to claim 1, characterized in that: The passivating agent comprises at least one of cassava starch, wheat starch and mung bean starch.
5. A method for preparing the AG flash effect frosting powder according to any one of claims 1 to 4, characterized in that: Mix all components in proportion.
6. Application of the AG flash effect frosting powder according to any one of claims 1 to 4 in glass etching.
7. The use according to claim 6, characterized in that The specific steps include: The AG flash effect frosting powder according to any one of claims 1 to 4 is added into water, stirred and dissolved, and then the glass to be etched is etched.
8. The use according to claim 7, characterized in that The mass ratio of frosting powder: water is 5:0.5-5:1.
5.
9. The use according to claim 7, characterized in that: The AG flash effect frosting powder according to any one of claims 1 to 4 is added into water, and then heated and stirred to accelerate dissolution.
10. The use according to claim 7, characterized in that: The etching process is performed at a temperature of 10-25° C., a frosting time of 60-90 seconds, and a frosting swing frequency of 1-2 times / second.